Sustentabilidade Organizacional: percepção de práticas sustentáveis nos ambientes de trabalho remoto e presencial entre os servidores Técnico-Administrativos em Educação do Instituto de Ciências Exatas e Naturais da UFPA - BEZERRA, Thiago de Matos (Universidade Federal do Pará, 2023)
Discussions on better use of natural resources and the global event of the COVID-19 pandemic have contributed to the expansion of changes in ways of working, so that organizations have had to adapt. In this context, there has been an expansion of remote work. In this way, a case study was carried out, with the aim of understanding how we arrived at sustainability practices in the work environment, in remote and face-to-face modalities. This is a cross-sectional study, of a descriptive nature, with pending information from a questionnaire with questions with open and closed answers, which was carried out among the load servers belonging to the career of the TechnicianAdministrative in Education, who work at the Instituto of Exact and Natural Sciences at the Federal University of Pará. The results indicated some awareness on the part of the public servants regarding this topic, regarding the similarity between the responses received in each modality, and indicated the need for the institution to continue to invest in the implementation of sustainability practices.